Human heredity : Principles and issues - Cummings, Michael R. (Australia: Thomson Learning, 2003)
The clear, readable, concise, highly polished and refined writing is a traditional strength of HUMAN HEREDITY: PRINCIPLES AND ISSUES. Complex topics and important concepts are presented with great clarity and precise logic, without oversimplifying the topic. In this beautifully illustrated and thoroughly revised new edition, Michael Cummings guides students toward understanding the hows and whys of genetic topics and new discoveries. Using an accessible writing style to explain complex concepts, Cummings includes the right balance of detail at the right level for nonscience students. In addition, he helps student see the social, cultural, and ethical implications associated with the use of genetic technology. In light of the recent developments in these fields (completion of the human genome), Cummings has incorporated such newly acquired "knowledge" and the resulting modern methods and& technology not only in Chapter 13, but also throughout the book, wherever applicable, as a kind of "thematic update." (Before, genetics was research/experiment-driven. Now, it has become data-driven, hence the term "data mining." This edition will also feature a significantly stronger Web integration, mostly built around providing students with the appropriate tools to master the thinking skills needed to learn human genetics. The earlier chapters will feature a web-based "toolbox" which will walk students through the process of understanding, analyzing, and working out problems, and which will in turn enable them to understand the various difficult genetics concepts in the later chapters.
Includes bibliographical references; Appendix A-B, 489-501p.; Glossary 502-509p.; Index 512-520p.
Keywords: Cytogenetics; DNA structure; Human heredity; Sex determination; Genetics